Three-dimensional magnetic resonance imaging overlay to assist with percutaneous transhepatic access at the time of cardiac catheterization - Wendy Whiteside; Jason Christensen; Jeffrey D Zampi (Wolters Kluwer Medknow Publications, 2015)
Multimodality image overlay is increasingly used for complex interventional procedures in the cardiac catheterization lab. We report a case in which three-dimensional magnetic resonance imaging (3D MRI) overlay onto live fluoroscopic imaging was utilized to safely obtain transhepatic access in a 12-year-old patient with prune belly syndrome, complex and distorted abdominal anatomy, and a vascular mass within the liver.